National Road Slide Management With Cantilever Type Soil Retaining Wall - Muda, Anwar (Jurnal Teknik Sipil, 2022)
The title of this research is "National Road Avalanche Management With Cantilever Type Soil Retaining Wall". The background of the research is that the national road sta 20+700, section 041 or to be precise in Muaramais Village, Tambangan District, Mandailing Natal Regency, North Sumatra, is a landslide point that occurred around 2018. For this reason, in 2021, handling has been carried out in landslides with a cantilever type retaining wall. The dimensions of the cantilever are 15 meters long, 3.50 meters deep from the asphalt surface and 2.00 meters wide. Then, the upper wall thickness is 0.30 meters and the lower wall thickness is 0.40 meters. The purpose of this study was to calculate whether the cantilever type retaining wall is safe against overturning, sliding and soil bearing capacity. The results of the research, that the cantilever type retaining wall is safe against overturning, because FS rolls = 4.65 ≥ FS = 2.00 and stability against shear is also safe, because FS shear = 1.96 ≥ FS = 1.50 and retaining walls safe against the bearing capacity of the soil, because the bearing capacity FS = 9.30 ≥ FS = 3.00